2023
DOI: 10.3390/cells12162051
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic Acetylcholine Receptor Dysfunction in Addiction and in Some Neurodegenerative and Neuropsychiatric Diseases

Abstract: The cholinergic system plays an essential role in brain development, physiology, and pathophysiology. Herein, we review how specific alterations in this system, through genetic mutations or abnormal receptor function, can lead to aberrant neural circuitry that triggers disease. The review focuses on the nicotinic acetylcholine receptor (nAChR) and its role in addiction and in neurodegenerative and neuropsychiatric diseases and epilepsy. Cholinergic dysfunction is associated with inflammatory processes mainly t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 228 publications
0
10
0
Order By: Relevance
“…Due to the limited efficacy and/or complications of current interventions, extensive effort, particularly towards the prevention of neurodegeneration, has been expended. In this regard, neuronal nAChRs have emerged as a viable target [ 4 , 34 , 35 ]. Interestingly, a mutation in RIC3, a chaperone of neuronal nicotinic acetylcholine receptor subunit α-7 (CHRNA7), was implicated in PD [ 7 ].…”
Section: Pd Pathophysiology and Current Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the limited efficacy and/or complications of current interventions, extensive effort, particularly towards the prevention of neurodegeneration, has been expended. In this regard, neuronal nAChRs have emerged as a viable target [ 4 , 34 , 35 ]. Interestingly, a mutation in RIC3, a chaperone of neuronal nicotinic acetylcholine receptor subunit α-7 (CHRNA7), was implicated in PD [ 7 ].…”
Section: Pd Pathophysiology and Current Treatmentsmentioning
confidence: 99%
“…It is now evident that nAChRs not only play an important role in neuronal function and the addiction to nicotine [ 151 , 152 ] but may also serve as targets for therapeutic intervention in various neuropsychiatric/neurodegenerative disorders, including PD [ 25 , 153 , 154 ], depression [ 153 , 155 , 156 ], obsessive–compulsive disorder [ 157 , 158 ], ADHD [ 159 ], Tourette syndrome [ 160 , 161 , 162 ], mild cognitive impairment or Alzheimer’s disease [ 163 , 164 , 165 , 166 ], ischemia [ 167 ], catalepsy [ 168 ], schizophrenia [ 4 , 166 , 169 ], pain [ 147 , 170 ], energy balance [ 171 , 172 ], autoimmune disorders [ 173 ], and even sleep–wake cycle dysregulation [ 174 ]. These receptors are also expressed abundantly in a variety of immune cells, including B cells, T cells, macrophages, and microglia, and are believed to contribute to the anti-inflammatory effects of nicotine [ 175 , 176 , 177 , 178 ].…”
Section: Nachrsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the limited efficacy and/or complications of current interventions, extensive effort, particularly towards the prevention of neurodegeneration, has been expended. In this regard, neuronal nAChRs have emerged as a viable target [4,34,35]. Interestingly, mutation in RIC3, a chaperone of neuronal nicotinic acetylcholine receptor subunit α-7 (CHRNA7), has been implicated in PD [7].…”
Section: Pd Pathophysiology and Current Treatmentsmentioning
confidence: 99%
“…Non-motor symptoms such as cognitive difficulties, depression, fatigue, sleep problems, urinary problems, constipation, and variations in blood pressure do not respond to what might be termed as "DA-replacement therapy." Thus, it is concluded that deficiencies in other neurotransmitter systems including nicotinic cholinergic system, may underlie these features [2][3][4]. As such, there is interest in targeting these other neurotransmitters functions to treat specific dopamine-resistant aspects of PD.…”
Section: Introductionmentioning
confidence: 99%